(untitled) (Nordic Journal of Practical Theology, 2020)
This article discusses how aspects of anomalous experiences can be understood in theology and psychology and investigates the premises on which dialogues between the two disciplines may facilitate more nuanced interpretations of such experiences. Two key issues are focused on: how anomalous experiences can be interpreted as religious experiences, and how they are connected to mental health. By relating empirical studies of anomalous experiences to interdisciplinary theoretical reflections, it is argued that there is a potential in the dialogue to buffer reductionist tendencies in the two, separate disciplines. Holding a repertoire of different interpretations on these issues is further considered to be beneficial in professional practice when encountering people with anomalous experiences.